Influence of Weather and Purity of Plasticizer on Degradation of Cassava Starch Bioplastics in Natural Environmental Conditions - Ahimbisibwe, Michael; Banadda, Noble; Seay, Jeffrey; Nabuuma, Betty; Atwijukire, Evans; Wembabazi, Enoch; Nuwamanya, Ephraim (Journal of Agricultural Chemistry and Environment, 2019)
The threat posed by plastics to the environment has prompted the development of bioplastics. Starch plasticized by glycerol is a key renewable resource in the production of high-quality bioplastics. Previous studies have availed information on the mechanical quality of starch-based bioplastics however there is limited information about their degradation pattern in the natural environment which this research presents. Bioplastics were buried in holes in loam sandy soil and weekly photographic data and weight were collected to reveal the effect of degradation. Weather parameters of rainfall, temperature, relative humidity, sunshine intensity and sunshine hours were recorded to establish influence of weather on degradation. A control set up in the laboratory was used to compare the results. Over time the tests revealed that as the hydrophilic enzymes break down the bioplastic, its weight initially increases (up to 87%) due to absorption of moisture and after saturation, the bioplastic is disintegrated which initiates decomposition and the bioplastic weight is steadily reduced. Degradation was further enhanced by invasion of soil organisms like worms, termites among other soil microbes. Rainfall (r = 0.857) increased the moisture in the soil which initially increased the weight of the bioplastic up to a point when the hydrophilic enzymes set into breakdown the bioplastic then the weight started to drop. This was the same case for relative humidity (r = −0.04) however; the sunlight intensity (r = 515) and hours of illumination indirectly affect the process by influencing microbial activity. An increase in the sunshine intensity increased the activity of soil organisms up to a point beyond which increased exposure caused the organisms to burrow deeper in the soil. Increase in microbial activity increased the rate of degradation of the buried bioplastics which took five to ten weeks to fully decompose (98.3%). The reduced time of degradation means that starch-based bioplastics have a high potential as sustainable substitute for petroleum-based plastics.
Keywords: Bioplastic, Degradability, Purified Glycerol